2018
DOI: 10.1186/s40643-018-0204-x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterizations of a novel recombinant Bacillus velezensis endoglucanase by aqueous two-phase system

Abstract: Background: Cellulases played an important role in the production of bioenergy and bio-products. Cellulases from bacteria with some special characteristics drew great attention due to its fast growth speed, wide adaption to harsh environment, and production of multi-function cellulases.Results: An endoglucanase gene egls from Bacillus velezensis A4 was cloned and expressed in Escherichia coli BL21 (DE3). The recombinant enzyme Egls was partially purified using aqueous two-phase system. The highest recovery rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(38 reference statements)
0
4
1
Order By: Relevance
“…6a). This value is higher than the optimum pH for the previously published β-1,3-1,4-D-glucanase from B. velezensis ZJ20 (pH 5.0) (Xu et al 2016), and slightly higher than the endoglucanase from B. velezensis A4 (pH 5.0-6.0) (Liu et al 2018). Activity was still relatively high at pH 5.5 (over 85% of the optimum) as well as at pH 7.0 (70%) and 7.5 (50%).…”
Section: Determination Of Optimal Ph and Temperaturecontrasting
confidence: 60%
See 2 more Smart Citations
“…6a). This value is higher than the optimum pH for the previously published β-1,3-1,4-D-glucanase from B. velezensis ZJ20 (pH 5.0) (Xu et al 2016), and slightly higher than the endoglucanase from B. velezensis A4 (pH 5.0-6.0) (Liu et al 2018). Activity was still relatively high at pH 5.5 (over 85% of the optimum) as well as at pH 7.0 (70%) and 7.5 (50%).…”
Section: Determination Of Optimal Ph and Temperaturecontrasting
confidence: 60%
“…Egl-257 from B. circulans KSM-N257 was also able to hydrolyze lichenan and CMC and was classified as a true endo-1,4-glucanase, despite showing 76.3% similarity to a lichenase from B. circulans WL-12 (Hakamada et al 2002). The substrate specificity of the purified H1 endoglucanase differs from that of the 55-kDa endoglucanase from B. velezensis A4 (activity only on CMC, filter paper, and avicel) (Liu et al 2018), and the 54-kDa endoglucanase from B. amyoliquefaciens DL-3, which was able to degrade all substrates tested in our study, but showed higher activity on CMC (Lee et al 2008).…”
Section: Substrate Specificity and Reaction Productsmentioning
confidence: 94%
See 1 more Smart Citation
“…Variations in the usage of solubility tags/signal peptide are also reported by some researchers. Amore et al [17] and Liu et al [29] used signal peptide of source organism whereas Kim et al [30] expressed cellulase on the outer membrane of E. coli in fusion with ice nucleation protein (membrane protein of P. syringae).…”
Section: Discussionmentioning
confidence: 99%
“…The study of genomes allows the targeted cloning of the desired gene to produce an enzyme with good stability, high activity, and a high yield [28] . The significance of cloning and expression of the enzyme genes is shown in Fig.…”
Section: Bioinformatics Study Of B Velezensismentioning
confidence: 99%